Training and Pruning Florida Peaches, Nectarines, and Plums - James Ferguson (EDIS)
HS-1111, a 5-page illustrated fact sheet by J. Ferguson, explains for both homeowner and commercial grower audiences the concepts underlying recommended tree training and pruning as well as related fruit thinning practices. Published by the UF Department of Horticultural Sciences, July 2007.